Effect of Sustained Systemic Administration of Ginger (Z officinale) Rhizome Extracts on Salivary Flow in Mice - Chang Yu Kan; Jing Xuan H'ng; Andy Goh; Frederick Smales; Eng Lai Tan; Shiming Zhang; Mallikarjuna Rao Pichika; Abhishek Parolia (Elsevier, 2023)
Objective: This study aimed to evaluate the effect of methanol (70% v/v), ethanol (80% v/v), dimethyl sulfoxide (DMSO; 100% v/v) extracts of ginger rhizome (GR), and 6-shogaol on the pilocarpine-stimulated salivary flow rate in C57BL/6 mice. Methods: Three extracts of ginger (Zingiber officinale) rhizome prepared by maceration using the respective solvents and 6-shogoal were reconstituted in normal saline with 0.2% DMSO. Thirty C57BL/6 15-week-old mice were divided into 5 groups: Group 1, saline; Group 2, 70% methanol extract; Group 3, 80% ethanol extract; Group 4, 100% DMSO extract; and Group 5, 6-shogaol. The baseline pilocarpine-stimulated salivary flow rate was measured at the age of 15 weeks (15th week), and treatment solutions were administered by intraperitoneal injection from the 16th to 18th week. The stimulated salivary flow rate during treatment weeks was recorded for each group, and its difference with baseline was analysed using paired-sample t test. The change in salivary flow rate between the treatment groups and the control group was analysed using one-way analysis of variance. Results: Groups 2, 3, 4, and 5 showed a significant increase in salivary flow rate when compared to baseline (P < .05). The increase in salivary flow rate in all 4 treatment groups was significant when compared to the control group (P < .05). Group 4 produced the highest increase in salivary flow rate; however, the differences amongst the treatment groups did not reach statistical significance (P > .05). Conclusions: All GR extracts (70% methanol, 80% ethanol, 100% DMSO) and 6-shogaol were equally effective in increasing the pilocarpine-stimulated salivary flow rate in C57BL/6 mice when administered systemically as a sustained dose for 3 weeks.